The Effects of population factors on social and economic development - National Population Bureau, Nigeria (Nigeria : National Population Bureau, 1985)
This study examine the population dynamics and the social and economic development objectives of Nigeria and explores the impact of varying rates of population growth on national development
Prepared under the direction of the Federal Ministry of Health and the National Population Bureau
Includes bibliographical references (p. 50-51).
osc 20/05/2019
Arch
Keywords: Population forecasting; Economic forecasting; Economic development; Nigeria